Systematic Literature Review: Development of Digital Marketplace Platforms Based on Islamic Legal Principles - Haryanto, Didik; Hoiri, Muhamad Nur; Suryono, Ryan Randy (Universitas Nurul Jadid, 2026)
The development of digital marketplaces has transformed how people conduct economic transactions, including within the context of Islamic economics, which requires compliance with Sharia principles. Although digital technology has been widely adopted in digital marketplaces, it generally remains oriented toward efficiency and profit, and thus has not yet been fully able to implement the values of fiqh muamalah comprehensively. Therefore, this study aims to examine in depth how technology can be utilized as a normative system that supports Sharia compliance in digital marketplaces. This research employs a Systematic Literature Review (SLR) method to analyze scholarly articles related to Sharia-compliant e-commerce, digital payment systems, Islamic business ethics, and technology management. The literature was selected through stages of identification, screening, and thematic synthesis to obtain a comprehensive overview of technological solutions and the challenges of meeting Sharia requirements. The distinct contribution of this study lies in its emphasis that technology should be designed as a system embedded with specific values, rather than merely as a technically neutral tool. However, the implementation of Sharia-oriented technology still faces various challenges, such as algorithmic limitations, low levels of Sharia understanding, and the absence of integrated Sharia standards within digital regulations across different countries. This study concludes that Sharia compliance in digital marketplaces can only be achieved through an integrated approach that combines systems engineering, value-based organizational management, and the institutional implementation of Sharia regulation, so that digital transformation can align with the principles of justice, transparency, and benefit for the Muslim community within Islamic economics.